2020
DOI: 10.1111/1440-1703.12176
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche modeling for assessing potential distribution ofPterocarpus marsupiumRoxb. In Ranchi, eastern India

Abstract: The present study was conducted to predict the current and future potential distribution of a tree species Pterocarpus marsupium Roxb. in Ranchi, Eastern India using ecological niche modeling. Nine environmental variables comprising of isothermality, precipitation of wettest and warmest quarter, annual temperature range, soil type, human influence index, elevation, slope and land use cover were used to model the distribution of the species. Climatic variables governed the predicted distribution of the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…, to identify the most probable distribution of the species. Over the years, Maxent software has emerged as one of the most promising and authentic tools to study the habitat suitability of various categories of tree species globally including dry deciduous species (Chitale and Behera 2012 ; Deb et al 2017 ; Kumar et al 2020 ; Torlap and Lamthai 2019 ). Therefore, the present study was persuaded with the objective to identify the most suitable habitat of B. monosperma for chalking out strategies for its conservation and promotion of lac cultivation and socio-economic amelioration.…”
Section: Introductionmentioning
confidence: 99%
“…, to identify the most probable distribution of the species. Over the years, Maxent software has emerged as one of the most promising and authentic tools to study the habitat suitability of various categories of tree species globally including dry deciduous species (Chitale and Behera 2012 ; Deb et al 2017 ; Kumar et al 2020 ; Torlap and Lamthai 2019 ). Therefore, the present study was persuaded with the objective to identify the most suitable habitat of B. monosperma for chalking out strategies for its conservation and promotion of lac cultivation and socio-economic amelioration.…”
Section: Introductionmentioning
confidence: 99%
“…This creates competition and the alteration of the ecosystem balance, resulting in a poor population in disturbed sites. Kumar et al [74] observed the skewed population structure of P. marsupium in the central and eastern zone of India due to poor natural regeneration, which was a result of anthropogenic factors and the vigorous growth of associated species. Regional-scale climate change in tandem with deforestation and habitat unsuitably are also responsible for the declined population of P. marsupium from it natural geographical ranges in India [75].…”
Section: Species Compositionmentioning
confidence: 99%
“…It is also beneficial for treating jaundice, fever, wounds, diabetes, stomach aches, and ulcers [4]. Nonetheless, anthropogenic overexploitation of genetic resources, along with poor natural regeneration, survival, and growth rates, has elevated the probability of species extinction [5]. A number of species from the same genus have already been red-flagged by the concerned authorities.…”
Section: Introductionmentioning
confidence: 99%